Bιβλιοκρισία του: P. ANTONOPOULOS, The Reign of Cunincpert. Saga, Reality, Stability and Progress in Lombard Italy at the End of the Seventh Century, Porphyrogenitus Ltd, Camberley, Surrey 2010 - ΧΡΗΣΤΟΥ Κωνσταντίνος (Byzantina Symmeikta, 2012)
ΒΙβλιοκρισία του: P. ANTONOPOULOS, The Reign of Cunincpert. Saga, Reality, Stability and Progress in Lombard Italy at the End of the Seventh Century, Porphyrogenitus Ltd, Camberley, Surrey 2010, σσ. Χ+138 (ΙSBN 1 871328 18 7).